Pelatihan Quantum TeachingUntuk Meningkatkan Kreativitas Mengajar Guru Di Mts Al-Irsyad Tengaran - Hag, Akhmad Liana Amrul, Dr Lisnawati Ruhaena, M.Si.., Psikolog, Dra. Juliani Prasetyaningrum, M.Si (2016)
This research has the purpose to know the effectiveness of quantum teaching training in improving teachers‟ teaching creativity. Subject of this research was the teachers who teach in MTS Al-Irsyad, with the total amount of 33 people which were divided into three treatment groups, i.e. xperimental group, control group 1 and control group 2. Research data gathering used scale of teaching creativity and research which used the Solomon three group design, The data analysis result which was gained by using Mann Whitney U showed that posttest score between experimental group with control group 1 was Z -2,141 with the significant asymp. 0,032 (p>0,05). The posttest score result between experiment group witg control group 2 was Z -1,151 with the significant asymp.0,250 (p>0,05) and the pottest score result between control group 1 and control group 2 was Z -,395 significantAsymp. 0,693 (p>0,05).based on the analysis result above, it was found that the training of Quantum Teaching was effective to improve teaching creativity of teachers in MTs Al-Irsyad, the teachers who attended the training of Quantum Teaching had better teaching creativity than the teachers who did not attend the training of Quantum Teaching Keywords: quantum teaching, teaching creativity, solomon